Interoception and sexual response in women with low sexual desire. - Julia Velten; Lori A Brotto (PLoS ONE, 2017)
Sexual concordance is defined as the association between genital response and self-reported sexual arousal. Though one might predict a strong association between sexual concordance and awareness of other internal physiological sensations (termed interoception), past research on sexually healthy women has not found these different domains to be related. The aim of the present study was to test the association between interoception and sexual concordance in a clinical sample of women with Sexual Interest/Arousal Disorder (SIAD). Fifty-two women with SIAD completed the Multidimensional Assessment of Interoceptive Awareness (MAIA), a validated self-report measure of interoception, and completed a heart-beat accuracy test, an objective measure of interoception. They also participated in a laboratory-based assessment of physiological sexual arousal and self-reported sexual arousal while viewing an erotic film. Mental and physiological arousal were correlated at r = 0.27 (range -0.80 to 0.95). There was no significant association between sexual concordance and women's heartrate awareness. However, five aspects of interoceptive awareness (noticing, emotional awareness, self-regulation, body-listening, and trusting), were predictive of lower, and one aspect (not-distracting) was predictive of higher sexual concordance. We discuss the findings in relation to the role of emotions and arousal states in the interoception-sexual concordance relationship.